Yearly cycle of lower tropospheric ozone at the Arctic Circle - Rummukainen, Markku ; 0000-0001-5709-9804; Laurila, Tuomas; Kivi, Rigel (Atmospheric Environment, 1996)
Measurements of tropospheric ozone at three sites at the Arctic Circle in the Finnish Lapland are presented. The variability of ground-level ozone over the diurnal and seasonal cycles in 1992-93 is discussed for the sites of Oulanka and Pallas. The variability with height and over the annual cycle in 1989-94 is discussed for the Sodankyla aerological Observatory, which has the longest record on the vertical distribution of ozone in the Nordic region. Seasonally resolved ozone statistics and the differences between the sites are accounted for. At the surface, ozone levels peak in the spring, but they decline rapidly in the early summer (remote area feature) with a 15-30% seasonal difference. The seasonal difference between spring and summer decreases with height in the lower troposphere and at 850 and 700 hPa, the spring maximum continues as high ozone levels in the summer (an anthropogenic feature). At these two levels, the relative differences in ozone between spring and summer were 4% and -1.3%, respectively. The summertime high ozone levels in the lower troposphere highlight the importance of transport of anthropogenic precursors of ozone for the regional lower troposphere. A three-dimensional trajectory climatology is used for assessing tropospheric transport patterns. Air mass transport occurs from both remote and polluted source regions. The Arctic is the most important source region at the 950 hPa level. With increasing altitude, the contributions of the European and the Atlantic regions become comparable. The evolution of snow cover and surface-based inversions affect the variability of ozone, through variations in the deposition sink strength and the boundary layer stability.
Keywords: Arctic; Long-range transport; Tropospheric ozone